Geographic gradients in a functional trait: variation of body size and size diversity in ground beetle Poecilus cupreus (Linnaeus, 1758) (Coleoptera, Carabidae) - Raisa A. Sukhodolskaya; Sergey L. Luzyanin; Teodora M. Teofilova; Vladimir Landgraf; Nadezhda L. Ukhova; Tamara A. Avtaeva; Kirill Yu. Maksimovich; Andrey D. Belosludcev; Roman P. Gorbunov (Acta Biologica Sibirica)
The aim of this study was to test the character of body size variation and its diversity in the widespread ground beetle Poecilus cupreus in geographical gradients. Beetles were sampled in 14 regions of Europe and the Asia, and sampling territories differed by 17° in latitude and 121° in longitude. We measured six linear traits in each captured beetle and formed a data set that included 6745 individuals. In the latitudinal gradient, three of the six traits studied decreased their values (direct trends), and the variability curve of four of the six features studied is hump-shaped with a maximum value in the middle latitudes (polynomial trends). In the longitudinal gradient, three traits decreased their values (direct trends), and the variability of three ones had the form of a concave curve with minimum values in the middle longitudes. The variability coefficients of the features themselves behave differently. Their value increased in the latitudinal gradient and decreased in the longitudinal gradient (direct trends). Polynomial trends show a hump-shaped curve – the greatest variability of feature values is observed in the middle latitudes and middle longitudes. We worked according to a single methodology and our analysis is intraspecific, so we insist that such eco-geographic and morphometric studies be conducted in the same way.